2007
DOI: 10.1007/s10439-007-9292-z
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Dependent Neurite Outgrowth and Response to Dynamic Deformation in Three-Dimensional Neuronal Cultures

Abstract: Abstract-In vitro models of brain injury that use thick 3-D cultures and control extracellular matrix constituents allow evaluation of cell-matrix interactions in a more physiologically relevant configuration than traditional 2-D cultures. We have developed a 3-D cell culture system consisting of primary rat cortical neurons distributed throughout thick (>500 lm) gels consisting of type IV collagen (Col) conjugated to agarose. Neuronal viability and neurite outgrowth were examined for a range of agarose (AG) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 62 publications
5
85
0
Order By: Relevance
“…However, several studies have indicated that it may be an initiator of TBI. In an in vitro study, quick deformation of three-dimensional collagen gels led to a decrease in embedded neuronal viability when the collagen concentration increased, indicating the potential impact of cell-ECM interactions on injury (82). Another study suggested that ECM influences axonal injury by activating Rho signaling pathways; up-regulation of RhoA was accompanied by fluid percussion brain injury (83).…”
Section: Microenvironmentmentioning
confidence: 99%
“…However, several studies have indicated that it may be an initiator of TBI. In an in vitro study, quick deformation of three-dimensional collagen gels led to a decrease in embedded neuronal viability when the collagen concentration increased, indicating the potential impact of cell-ECM interactions on injury (82). Another study suggested that ECM influences axonal injury by activating Rho signaling pathways; up-regulation of RhoA was accompanied by fluid percussion brain injury (83).…”
Section: Microenvironmentmentioning
confidence: 99%
“…Moreover, the ECM components and cellular distribution are difficult to control in reaggregate cultures; however, these models are extremely useful for studying cell-cell interactions, growth, and function at cell densities that closely match those found in vivo. Three-dimensional cell culture models consisting of neural cells distributed throughout a matrix have also been developed [13,[15][16][17][30][31][32]. In these systems, trade-offs exist between culture thickness (i.e., surface area to volume ratio), and hence the scope of 3D spatial interactions, and cell density, necessitating that relatively thick ([500 lm) cultures use cell densities at least an order of magnitude lower than that found in brain cortices [32,33].…”
Section: Dissociated Cell Culturesmentioning
confidence: 99%
“…Three-dimensional cell culture models consisting of neural cells distributed throughout a matrix have also been developed [13,[15][16][17][30][31][32]. In these systems, trade-offs exist between culture thickness (i.e., surface area to volume ratio), and hence the scope of 3D spatial interactions, and cell density, necessitating that relatively thick ([500 lm) cultures use cell densities at least an order of magnitude lower than that found in brain cortices [32,33]. However, using these 3D scaffold-based neural cultures, key parameters governing neuronal survival and neurite outgrowth based on scaffold physical/biological properties and mass transport phenomena have been uncovered.…”
Section: Dissociated Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations